2000
DOI: 10.22358/jafs/68040/2000
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of microbial protein supply in ruminant animals based on renal and mammary purine metabolite excretion. A review

Abstract: The potential of mammary and renal purine metabolite excretion as a technique for the assessment of microbial protein supply in ruminant animals is reviewed. Data reported in the literature tends to support the validity of the assumptions of the technique that purines entering the duodenum are essentially microbial in origin and that following metabolism, purine catabolites (collectively allantoin, hypoxanthine, uric acid and xanthine) are quantitatively recovered in urine. The most convincing experimental evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 113 publications
2
28
0
Order By: Relevance
“…Samples were cooled on ice, transported to the laboratory, and frozen until analysis. Purine derivative-to-creatinine ratio (PD:CR) was used as an indicator of relative changes in rumen microbial flows to the intestinal tract (Valadares et al, 1999;Shingfield, 2000;Whittet et al, 2004). Creatinine and purine derivatives were determined using HPLC (Waters Corp., Milford, MA) according to the procedure of Shingfield and Offer (1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were cooled on ice, transported to the laboratory, and frozen until analysis. Purine derivative-to-creatinine ratio (PD:CR) was used as an indicator of relative changes in rumen microbial flows to the intestinal tract (Valadares et al, 1999;Shingfield, 2000;Whittet et al, 2004). Creatinine and purine derivatives were determined using HPLC (Waters Corp., Milford, MA) according to the procedure of Shingfield and Offer (1999).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, PD:CR in spot urine samples can be used to estimate microbial production. Shingfield (2000) concluded that with current understanding, purine degradation products may be used to determine relative differences in microbial production -absolute values will require more research. We are therefore reporting PD:CR as an indicator of treatment effects on microbial production.…”
Section: Purine Derivativesmentioning
confidence: 99%
“…The conversion of degradable protein into MP in the rumen requires the contribution of energy for ruminal microorganisms (Beever and Cottrill, 1994;Firkins et al, 2007). Microbial protein production is generally considered proportional to the energy available for fermentation in the absence of acidosis; however, the efficiency of microbial protein synthesis (EMPS) is affected by other factors, including those that emphasize feeding level and ruminal synchrony (Dewhurst et al, 2000;Shingfield, 2000). The use of diets with a high nonstructural carbohydrate content increases passage rate, the supply of metabolizable energy and intestinal digestible protein, and EMPS (Firkins et al, 2006).…”
mentioning
confidence: 99%
“…Some of these are based on measurements of digesta flow, which requires fistulated animals and microbial markers, thereby rendering these methods questionable from the point of the animal's well-being (Shingfield, 2000;González-Ronquillo et al, 2004). There are also discrepancies between estimations of microbial N flow towards the duodenum with the use of different markers (Shingfield, 2000). The estimation of MPS from purine derivatives (PD) in the urinary excretion is a simple and non-invasive method that needs only the quantitative collection of urine.…”
mentioning
confidence: 99%
“…Theoretically, purine derivative:creatinine ratios are indicative of microbial growth in the rumen (Shingfield, 2000), and if fat content of the diet was the reason for decreased BW gain in the infrequently supplemented treatment, a decreased purine derivative:creatinine ratio would be expected. Purine derivative:creatinine ratio may not be an accurate determinant of absolute quantities of microbial purine production, but has been shown to be useful in determining relative differences in purine production among treatments (Shingfield, 2000). The ratio of purine derivatives:creatinine was not different (P = 0.12) between treatments in this experiment.…”
Section: Experiments 2: Heifer Performance Trialmentioning
confidence: 99%